Analysis of the Influence of Product Quality, Brand Image and Country of Origin on Purchase Decision of Xiaomi Mobile Phone Products - Frans Sudirjo; Henny Dwijayani; Ana Fitriyatul Bilgies; Andriya Risdwiyanto; Nurlaili Rahmi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study aims to determine how nation of origin, product quality, and brand image affect purchasing decisions. This study uses quantitative case study research techniques. Primary data were gathered for this study through questionnaires and incidental sampling methods. Multiple linear analysis utilizing the statistical product and service solutions (SPSS) 23 software was the data analysis method used in this investigation. The results of this study indicate that place of origin, product quality, and brand image all have a significant simultaneous and partial impact on buying decisions.